2011
DOI: 10.1074/jbc.m111.279711
|View full text |Cite
|
Sign up to set email alerts
|

Alsin and SOD1G93A Proteins Regulate Endosomal Reactive Oxygen Species Production by Glial Cells and Proinflammatory Pathways Responsible for Neurotoxicity

Abstract: Recent studies have implicated enhanced Nox2-mediated reactive oxygen species (ROS) by microglia in the pathogenesis of motor neuron death observed in familial amyotrophic lateral sclerosis (ALS). In this context, ALS mutant forms of SOD1 enhance Rac1 activation, leading to increased Nox2-dependent microglial ROS production and neuron cell death in mice. It remains unclear if other genetic mutations that cause ALS also function through similar Nox-dependent pathways to enhance ROS-mediate motor neuron death. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 51 publications
2
61
0
4
Order By: Relevance
“…In addition, several reports describe NOX2 as a source of damaging ROS in ALS (7,9,10,12). Consistent with this, in the present study we found a basal upregulation of the Rac1-NOX2 pathway in the model of SOD1-G93A primary microglia, in line with previous results obtained in cell lines transiently infected with ALS-related genes (7,12), and we also demonstrated that activation of the P2X 7 receptor further enhances this pathway, thus producing additional oxidative stress. Furthermore, by overexpression of a dominant-negative or constitutively active form of Rac1 in ALS microglia, we established that p67 phox subunit translocation on membranes is totally dependent on Rac1 recruitment and not on alternative pathways; thus, Rac1 activation is a prerequisite for NOX2 activation by the P2X 7 receptor.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, several reports describe NOX2 as a source of damaging ROS in ALS (7,9,10,12). Consistent with this, in the present study we found a basal upregulation of the Rac1-NOX2 pathway in the model of SOD1-G93A primary microglia, in line with previous results obtained in cell lines transiently infected with ALS-related genes (7,12), and we also demonstrated that activation of the P2X 7 receptor further enhances this pathway, thus producing additional oxidative stress. Furthermore, by overexpression of a dominant-negative or constitutively active form of Rac1 in ALS microglia, we established that p67 phox subunit translocation on membranes is totally dependent on Rac1 recruitment and not on alternative pathways; thus, Rac1 activation is a prerequisite for NOX2 activation by the P2X 7 receptor.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, in a previous work we demonstrated that the extracellular ATP pool is better preserved and the P2X 7 receptor is upregulated in SOD1-G93A microglia, which translates into an increase in released proinflammatory factors and neurotoxicity induced by microglia upon P2X 7 receptor stimulation (21). In addition, several reports describe NOX2 as a source of damaging ROS in ALS (7,9,10,12). Consistent with this, in the present study we found a basal upregulation of the Rac1-NOX2 pathway in the model of SOD1-G93A primary microglia, in line with previous results obtained in cell lines transiently infected with ALS-related genes (7,12), and we also demonstrated that activation of the P2X 7 receptor further enhances this pathway, thus producing additional oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As H 2 O 2 levels increase, thiols are reduced and thiolate-dependent enzymes are inhibited, leading to oxidative damage to lipids, proteins, and DNA. Furthermore, superoxide and NO released from activated microglia may act as exogenous toxins to motor neurons [41]. Oxidative stress probably accelerates disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…(171,182) and novel studies on the role of NOX isoforms in these new models are nowadays needed (107). Taken together, evidence from NOX2-(and, to a lesser extent, NOX1-) deficient mice suggest that NOX activation is causally involved in the progression of ALS.…”
Section: Studies In Humansmentioning
confidence: 93%